2004
DOI: 10.1016/j.mseb.2003.10.094
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen storage properties on mechanically milled graphite

Abstract: We investigated hydrogen absorption/desorption and structural properties in mechanically milled graphite under hydrogen pressures up to 6 MPa to clarify catalytic and hydrogen pressure effects in the milling. The results indicate that a small amount of iron contamination during milling plays a quite important role as a catalyst for hydrogen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 7 publications
1
50
1
1
Order By: Relevance
“…Then, we studied H-storage properties of mechanically milled graphite under some hydrogen pressures up to 6 MPa in order to know whether the intrinsic H-storage properties of graphite are improved or not by increasing the milling hydrogen pressure up to 6 MPa. 66,67) In Fig. 11, the TDMS profiles of hydrogen are shown for mechanically milled graphite at a frequency of 10 Hz for 80 h under various H 2 -gas pressures by a vibrating ball mill equipment, together with that for graphite milled at 400 rpm for 80 h under a H 2 -gas pressure of 1 MPa by a planetary ball mill method as well.…”
Section: Hydrogen Storage Properties Of Graphite Based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we studied H-storage properties of mechanically milled graphite under some hydrogen pressures up to 6 MPa in order to know whether the intrinsic H-storage properties of graphite are improved or not by increasing the milling hydrogen pressure up to 6 MPa. 66,67) In Fig. 11, the TDMS profiles of hydrogen are shown for mechanically milled graphite at a frequency of 10 Hz for 80 h under various H 2 -gas pressures by a vibrating ball mill equipment, together with that for graphite milled at 400 rpm for 80 h under a H 2 -gas pressure of 1 MPa by a planetary ball mill method as well.…”
Section: Hydrogen Storage Properties Of Graphite Based Materialsmentioning
confidence: 99%
“…On the other hand, the higher milling pressure gave suppression of the fracture rate of graphite structure more effectively, suggesting that the hydrogen atoms trapped at the edges of the graphene sheets and between the graphene sheets near the surface are responsible for preserving the lamellar structure of nanometer scale, which may be the host for H-storage on physisorption. 66,67) …”
Section: Appearance Of Physisorption-like Hydrogen Inmentioning
confidence: 99%
“…C nano H x is synthesized from graphite by the ball-milling under H 2 gas atmosphere. [13][14][15][16][17][18][19][20][21][22] So far, it has been reported that the hydrogenated nano-structural graphite (C nano H x ) can store about 7.4 mass% of hydrogen. 13 C nano H x material requires heating up to more than 700 C to release the hydrogen and desorbs hydrogen with hydrocarbons (CH 4 and C 2 H 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been experimentally confirmed that the maximum hydrogen concentration is 7 mass% in milled graphite. [12][13][14][15][16] This indicates that the amount of the hydrocarbon components in the thermally desorbed gases is abundant for nanostructural graphite milled by the rocking mill method because the hydrogen content does not depend on the milling method. From these results, it is concluded that the hydrogenated state in the nanostructural graphite is considerably affected by the milling conditions as well.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16] However, higher temperature than 700 C is necessary to release all of the chemisorbed hydrogen from C nano H x , because the covalent bond between C and H is too strong to desorb hydrogen. 17) In this paper, we report on the issues how to destabilize the Li-H and C-H bonds.…”
Section: Introductionmentioning
confidence: 99%